An Evaluation of Cyclic Loading Conditions and Computed Tomography for the Strength and Petrophysical Properties of Anhydrite Caprock (Rudarsko-geološko-naftni zbornik, 2021)
Underground gas storage (UGS) in depleted reservoirs affects caprock properties. The resemblance of Qom anhydrite outcrop with cutting obtained from a 2629 m depth was confirmed using X-ray diffraction (XRD) results and scanning electron microscope (SEM) tests. The anhydrite specimens unconfined compressive strength (UCS) changed under static cyclic loading conditions, and also petrophysical properties, such as porosity and permeability altered under 10, 20, and 30 cycles of loading. The magnitude of loading ranged from 30 to 43% of intact anhydrite UCS. The loading rate used for cyclic loading tests was 0.004 mm/s. The samples’ UCS decreased between 3.5 to 23.9% under cyclic loading conditions. The study of specimens computed tomography (CT) imaging with porosity and permeability indicated the growth of cracks, the cracks did not initiate in all lengths of specimens, hence the incremental increase in porosity did not increase the permeability of specimens. Even being under cyclic loads, the permeability of specimens stayed lower than 10-15 m2 (0.001 mD) but the trend of pressure versus time for measuring permeability shows a higher drop in pressure due to changes in permeability. The study indicated that the CT imaging results are in good accordance with petrophysical findings.